The Effect Of Bank Digitalization On Improving Service And Customer Satisfaction On Bank Mandiri - Panyabungan - Fahmi, Muhammad; L.R. Rangkuti, Maudy (CERED Indonesia Institute, 2024)
The purpose of this research is to determine the effect of improving services through bank digitalization on customer satisfaction at Bank Mandiri, Panyabungan, both directly and indirectly. The population in this research is Bank Mandiri Panyabungan customers who use bank digitalization, namely the Livin By Mandiri application. With a sample of 100 respondents. This research uses a quantitative approach. The data management used in this research is SemPLS 4. The results of this research show that Service Improvement has a positive and significant effect on Customer Satisfaction, Service Improvement has a positive and significant effect on Bank Digitalization, Bank Digitalization has a positive and significant effect on Customer Satisfaction, Service Improvement as an intervening variable is able to significantly mediate the influence of Bank Digitalization on Customer Satisfaction. The results of testing the R-Square value showed that the path model using intervening variables was 0.692 and 0.751. In other words, the ability of the variable X, namely Service Improvement, in explaining variable Z, namely Customer Satisfaction, is 69.2%, thus the model is classified as moderate (medium) and the ability of the variable X, namely Service Improvement, explains variable Y, namely Customer Satisfaction, is 75.1%, thus the model is classified as substantial (strong).